(untitled) (Palimpsesto, 2021)
Just as Anthropology has provided knowledge about the Colombian cultural diversity not only along the lines of the academy, the museum is a communication channel between the public and the museum collections. In consequence, in the museal field anthropology, with other disciplines, has been comprehend as a power-knowledge in the process of nation building. This analysis seeks to contribute to the understanding of the anthropology role in the nation formation through museums. For this reason, in this article we reflect about how the nation’s narrative is determined in some museums by the appropriation of anthropological knowledge by the state official discourse. The above, under the premise that the museum works as a state agent in charge of doing ‘state acts’ through the exercise of classification and regulation of populations.